Pathological Differences through Stem Cell Therapy to the Infarction area by Cerebral Artery Hypoxia - LEE, TAE-HOON (International Journal of Psychosocial Rehabilitation, 2020)
Background: Mouse embryonic stem cell could show alternative materials of neuron cell differentiation, positively increasing their effectiveness in the treatment of nervous symptom. We examined which embryonic stem cells (ESCs) may be showed to undergo neuronal differentiation. Methods: After neuronal induction, the phenotype of mESCs changed towards neuronal morphology and mESCs were inserted to the ventricle of the experimental animal brain. Intragraft cells translocated to several regions of the brain and cerebral infarction of brain artery occlusion showed their relocation to the damaged striatum and cortex. Findings: Intracerebral grafting of mESCs mostly improve sensory and motor nervous system of physical default in focal cerebral model. This study proved that grafted mESCs dislocate and develop in several infarction condition and decrease central nervous system injury after focal ischemia in animals. Improvements: We anticipate that transplantation of mESCs could suggest a strong grafting therapy for various neurological injury and degenerative diseases.